2015
DOI: 10.1016/j.etap.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Malathion-induced testicular toxicity is associated with spermatogenic apoptosis and alterations in testicular enzymes and hormone levels in male Wistar rats

Abstract: Please cite this article as: Geng, X., Shao, H., Zhang, Z., Ng, J.C., Peng, C.,Malathioninduced testicular toxicity is associated with spermatogenic apoptosis and alterations in testicular enzymes and hormone levels in male Wistar rats, Environmental Toxicology and Pharmacology (2015), http://dx.doi.org/10. 1016/j.etap.2015.01.010 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 25 publications
4
51
0
6
Order By: Relevance
“…Conversely, TQ had been protecting the testicular injuries and kept the levels of ALP and ACP around the normal activities as in the control group. The activity of testicular ACP was decreased in malathion-treated due to damage in testicular tissue [30]. The altered enzyme activities may be coming from the damaged seminiferous epithelium and the function of the Sertoli cell.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, TQ had been protecting the testicular injuries and kept the levels of ALP and ACP around the normal activities as in the control group. The activity of testicular ACP was decreased in malathion-treated due to damage in testicular tissue [30]. The altered enzyme activities may be coming from the damaged seminiferous epithelium and the function of the Sertoli cell.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo and in vitro studies suggest that malathion can produce deleterious effects on somatic and germ cells in mice . Malathion induces ovarian cycle irregularities by altering the number of estrus cycles and its phases, affecting female reproduction .…”
Section: Introductionmentioning
confidence: 99%
“…QLP administration partly restored the morphology of Leydig, Sertoli, and spermatogenic cells damaged by TGs. Since studies have shown that spermatogenesis and maturation are regulated by the gonadal axis, affected by oxidative stress and spermatogenesis-related genes [27][28][29][30], the effects of QLPs on reproductive hormones, oxidative stress and spermatogenesis-related gene TSSK2 were evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%